Feeding the critically ill child in intensive care units: a descriptive qualitative study in two tertiary hospitals in Ghana - Alhassan Sibdow Abukari; Angela Kwartemaa Acheampong (BMC, 2021)
Abstract Background Critically ill children require optimum feeding in the intensive care units for speedy recovery. Several factors determine their feeding and the feeding method to adopt to address this phenomenon. The aim of this study was to explore and describe the feeding criteria of critically ill children at the neonatal and paediatric intensive care units. Methods A descriptive qualitative design was used to conduct the study. Six focus group discussions were conducted, and each group had five members. In addition, twelve one-on-one interviews were conducted in two public tertiary teaching hospitals in Ghana and analyzed by content analysis using MAXQDA Plus version 2020 qualitative software. Participants were selected purposively (N = 42). Results The decision to feed a critically ill child in the ICU was largely determined by the child's medical condition as well as the experts' knowledge and skills to feed. It emerged from the data that cup feeding, enteral, parenteral, and breastfeeding were the feeding processes employed by the clinicians to feed the critically ill children. Conclusions Regular in-service training of clinicians on feeding critically ill children, provision of logistics and specialized personnel in the ICU are recommended to reduce possible infant and child mortality resulting from suboptimal feeding.